The Usage of Solar Energy for Domestic Purposes - Yu. N. Petrenko; A. M. Tresh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Actual application of solar energy in self-reacting devices for domestic purposes is considered in this paper.